SEMIOTIC ANALYSIS OF KAONASHI'S CHARACTER TRANSFORMATION IN THE MOVIE SPIRITED AWAY BY HAYAO MIYAZAKI - Dinan Difitrian; Sukmawati Saleh (Gorga : Jurnal Seni Rupa, 2024)
This research aims to analyze the symbolism of Kaonashi's character in the animated film "Spirited Away" by Hayao Miyazaki using a semiotic approach from Charles Sander Peirce's theory. This approach was chosen to reveal the deep meanings contained in Kaonashi's character through signs, objects, and interpretants contained in the movie. Semiotic analysis will show how these characters reflect internal and social conflicts, as well as how interactions with the environment affect character development. This research enriches the understanding of character design in animated films and its contribution to deeper and more meaningful narratives. The research method used is descriptive qualitative by analyzing data obtained from films, art books, behind-the-scenes videos, and various additional sources. The results show that Kaonashi's character undergoes three main stages of transformation that reflect changes in his identity and the meaning he carries. In the first stage, Kaonashi is depicted as a lonely and ignored figure, who simply stays on the bridge of the spirit world. In the second stage, Kaonashi becomes greedy and loses control while in the spirit bath, showing the negative impact of greed and the need for recognition. In the third stage, Kaonashi finds peace and acceptance at Zeniba's house, showing the transformation to a calmer and more accepted identity. The conclusion of this study is that Kaonashi represents emptiness, loneliness, and confusion of direction as interactions with the environment affect character development, as in the lives of people around the world.KEYWORDSsemiotics, character transformation, spirited awayAUTHORSDinan DifitrianSukmawati SalehREFERENCESAbramovitch, S. (2021). Hollywood Flashback: œSpirited Away Broke Records and Made Oscar History. Hollywoodreporter.Com. https://www.hollywoodreporter.com/movies/movie-news/spirited-away-film- oscars-records-history-1235052088/ Blazer, L. (2015). Animated Storytelling: Simple Steps For Creating Animation and Motion Graphics. Peachpit Press. Dewi, F. N., & Mutiaz, I. R. (2023). MUATAN BUDAYA CHINA DALAM DESAIN KARAKTER YUN JIN GAME GENSHIN IMPACT. Gorga : Jurnal Seni Rupa, 12(2), 295. https://doi.org/10.24114/gr.v12i2.49133 Halim, B., & Yulius, Y. (2023). ANALISIS SEMIOTIKA FERDINAND DE SAUSSURE PADA FILM œSELESAI. Gorga : Jurnal Seni Rupa, 12(1), 63. https://doi.org/10.24114/gr.v12i1.41423 Kartini, K., Fatra Deni, I., & Jamil, K. (2022). Representasi Pesan Moral Dalam Film Penyalin Cahaya. SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, Dan Antropologi, 1(3), 121“ 130. https://doi.org/10.54443/siwayang.v1i3.388 Khaira, F., Jamarun, N., & Minawati, R. (2022). Mise En Scene Dalam Film Surat Kecil Untuk Tuhan. Gorga : Jurnal Seni Rupa, 11(2), 288. https://doi.org/10.24114/gr.v11i2.37425 Miyazaki, H. (2002). The Art of Spirited Away. VIZ Media LLC. Nismoro, R. (2024). Analisis Perilaku Karakter Marisol Dalam Film A Man Called Otto Sebagai Representasi Kepedulian Sosial. 3, 26“46.Sasmita, U. (2017). Representasi Maskulinitas dalam Film Disney Moana (Analisis Semiotika Charles Sanders Pierce). Jurnal Online Kinesik, 4(2), 130.Selby, A. (2013). Animation. Laurence King Publishing. Tinarbuko, S. (2008). Semiotika komunikasi visual. Jalasutra. Weels, P., & Moore, S. (2016). The Fundamentals of Animation (2nd Editio). Fairchild Books. Wibowo, I. S. W. (2013). Semiotika komunikasi : aplikasi praktis bagi penelitian dan skripsi komunikasi (2nd ed.). Mitra Wacana Media. Yumielda, V. D., & Efi, A. (2023). Istano Basa Pagaruyung: The Functional Values of the Building Toward its Residents, The Social Community, and Educational Elements. Indonesian Research Journal in Education |IRJE|, 7(2), 450“465. https://online-journal.unja.ac.id/irje/article/view/28298 Yumielda, V. D., & Zulkifli, Z. (2022). Kajian Semiotika Peirce Pada Karya Seni Lukis di Sanggar Seni Rupa Simpassri. Visual Heritage: Jurnal Kreasi Seni Dan Budaya, 5(1), 28“38. https://doi.org/10.30998/vh.v5i1.6524 Yuniati, N. I. D., & Chudari, I. N. (2021). Analisis Nilai-nilai karakter dalam animasi riko the series sebagai alternatif pembelajaran karakter. Didaktika, 1(3), 469“478. https://doi.org/10.17509/didaktika.v1i3.38109